Pomegranate Productivity in Farmer Producer Organizations: A Socio-Economic Perspective - Pallavi Kolekar; R. V. Chavan; S. V. Bharati (Research Advances and Challenges in Agricultural Sciences Vol. 6, 2024)
The primary goal of this study is to enhance the farmers’ competitiveness and to increase their advantage in emerging the market opportunities. The investigation was carried out in 2022-23 to study the socio-economic status of Farmer producer organizations member farmers. The multistage sampling method was used for the selection 126 samples from the Western Region of Maharashtra, India. Statistical tools like arithmetic mean and multiple linear regression model was used to analyze the socio-economic status and its effect on productivity of FPO members. The results revealed that, overall average age of the farmers was 39.98 years with 8.76 years of experience. The education level of farmer was up to higher secondary. The average family size was 6.94 number of person with land holding of 3.56 years. The R2 was 99.80 which indicated that the productivity was influenced by all the variables together with 99 per cent.